Obsessive-compulsive disorder: cerebral calcium deficiency as a possible etiologic/pathogenetic factor — a case study - Oken, R.J. (Medical hypotheses, 1997)
Obsessive-compulsive disorder (OCD) is briefly characterized, and several of the hypothesized neuroanatomical and neurochemical substrates of this etiologically heterogeneous syndrome are noted. Importantly, alterations in the CNS balance of monoaminergic neurotransmitter systems are probably involved in the pathobiology of OCD. Inasmuch as calcium (Ca) concentration regulates neuronal neurotransmitter release, presynaptic Ca deficiencies can disrupt normal neurotransmission. Supporting this, a case report is presented of a subject with intermittent OCD and comorbid cardiac pathology for whose latter condition a regimen of increasing doses of a Ca channel blocker (CCB) greatly exacerbated the OCD. Upon reducing, then discontinuing the CCB dose, the OCD sympomatology was greatly ameliorated. It is suggested that minimal use of CCBs is indicated for OCD subjects and that, if possible, they be substituted with other drugs. In view of the widespread use of CCBs, this cerebral Ca deficiency hypothesis of OCD etiopathogenesis should be further tested by seeking other OCD subjects, especially from cardiology practices.